Lichenicolous fungi of the Sakhalin Region of the Russian Federation, including Lichenopeltella sakhalinensis sp. nov. (Trichothyriaceae, Dothideomycetes, Ascomycota) - Zhurbenko, Mikhail P.; Ezhkin, Alexandr K. (Phytotaxa, 2025)
Lichenopeltella sakhalinensis mainly growing on ±decaying thallus of Parmelia squarrosa is described as new to science from the Pacific Russia. Stigmidium heterodermiae is newly reported for Asia. Roselliniopsis phaeophysciae is new to the Russian Federation and first reported on Heterodermia. Homostegia piggotii is new to the Sakhalin Region of the Russian Federation. A first list of 44 species of lichenicolous fungi known from the Sakhalin Region of the Russian Federation is presented, which can be estimated as no more than 25% of their true regional diversity.